Implikasi Sengketa Impor Daging Ayam antara Indonesia-Brazil yang diputus oleh Dispute Settelment Body (DSB) di WTO - Egi Fauzan Fikri (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The World Trade Organization, hereinafter referred to as the WTO, is an international organization part of the Economic and Social Council as an important component in international trade. In carrying out international trade activities, a legal instrument is needed to ensure the sustainability of trade and facilitate the resolution of disputes that will be experienced by the international community. The trade dispute between Indonesia and Brazil was caused by Indonesia's policy of stopping chicken meat imports from Brazil since 2009, causing Brazil to suffer huge losses because it could not export chicken meat to Indonesia. From the chicken meat import policy in Indonesia, Brazil demanded that Indonesia had carried out trade protection which violated various WTO rules. Indonesia's defeat in the DSB-WTO Panel was due to the many Indonesian policies that violated the WTO agreement and the inability of Indonesian representative diplomacy to resolve the dispute.